2004
DOI: 10.1038/sj.bjc.6601912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of screening for breast cancer in high-risk women on health-related quality of life

Abstract: The effectiveness of intensive surveillance in women at high risk for breast cancer due to a familial or genetic predisposition is uncertain and is currently being evaluated in a Dutch magnetic resonance imaging (MRI) screening (MRISC) study, in which annual imaging consists of mammography and MRI. Unfavourable side effects on health-related quality of life may arise from this screening process. We examined the short-term effects of screening for breast cancer in high-risk women on generic health-related quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
63
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 38 publications
9
63
2
Order By: Relevance
“…In this study, the statistically significantly worse HRQoL just before the CT scan, compared with HRQoL at a neutral point of time before screening (T0), is similar to an earlier report on breast cancer screening (Rijnsburger et al, 2004); however, in the latter study it is unknown whether the self-reported health change exceeded the MID of half an s.d. As a result of a slightly unfavourable effect of CT scanning on HRQoL, we did not find any clinically relevant changes between the assessment points (T0 to T1 to T2 to T3).…”
Section: Discussionmentioning
confidence: 38%
See 2 more Smart Citations
“…In this study, the statistically significantly worse HRQoL just before the CT scan, compared with HRQoL at a neutral point of time before screening (T0), is similar to an earlier report on breast cancer screening (Rijnsburger et al, 2004); however, in the latter study it is unknown whether the self-reported health change exceeded the MID of half an s.d. As a result of a slightly unfavourable effect of CT scanning on HRQoL, we did not find any clinically relevant changes between the assessment points (T0 to T1 to T2 to T3).…”
Section: Discussionmentioning
confidence: 38%
“…(2) Is there a difference in HRQoL between those with an indeterminate baseline result and those with a negative result? We hypothesised that lung-cancer-specific distress scores just before baseline CT screening would be higher compared with scores acquired a few months before screening (Rijnsburger et al, 2004). Also, in subjects who received an indeterminate baseline result we expected higher levels of lungcancer-specific distress 2 months after screening (but before the 3-month follow-up scan) compared to those who received a negative result.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…We used a 10% reduction in QoL for women who would be cured from breast cancer, and a 50% QoL reduction for those not cured (Appendix 1). We assumed no effect of the screening process on QoL, if no cancers were detected (34).…”
Section: Cost-effectiveness Of Screening Under the Age Of 50mentioning
confidence: 99%
“…Studies by Warner and Rijnsburger et al have demonstrated no adverse effect of increased surveillance on anxiety, depression, distress, and quality of life. 59,60 Except for in patients with breast implants, both mammography and ultrasound should be performed in all patients, even if an MRI examination is performed. In addition, the evaluation of the patient should take into account not only these results but also clinical findings, ie, from clinical breast examinations.…”
Section: Mri As a Screening Tool For Breast Cancermentioning
confidence: 99%